Hubungan Pertambahan Berat Tubuh Ibu Hamil Terhadap Berat Janin Melalui Fetal Biometri Ultrasonografi: USG-Radiologi - Hidayat, Wahyu; Edy Widiatmoko, Mahfud (JURNAL TERAS KESEHATAN, 2025)
Ultrasound examination is one of the main modalities to be an important tool used to determine fetal growth and development in pregnant women such as fetal weight in order to prevent stunting, complications and other abnormalities so that they can be treated early, quickly and accurately for the health of the mother and fetus. Purpose :to determine the role of ultrasound in relation to weight gain of pregnant women and fetuses through Fetal Biometry. Method used a descriptive qualitative design, with a sample of 37 pregnant. Results: most fetuses over 30 weeks old weigh between 2500-3500 grams (normal). and there are some fetuses with lower weight (below 2500 grams), which may require further monitoring regarding the possibility of intrauterine growth restriction (IUGR). Conclusion: most pregnant women experienced weight gain in accordance with pregnancy standards, and there were several cases of low-weight mothers who needed more attention in terms of nutrition.